Environmental Stress-Induced Bacterial Lysis and Extracellular DNA Release Contribute to Campylobacter jejuni Biofilm Formation - Feng, Jinsong (Appl Environ Microbiol, 2018)
Campylobacter jejuni is a microaerophilic bacterium and is believed to persist in a biofilm to antagonize environmental stress. This study investigated the influence of environmental conditions on the formation of C. jejuni biofilm. We report an extracellular DNA (eDNA)-mediated mechanism of biofilm formation in response to aerobic and starvation stress. The eDNA was determined to represent a major form of constitutional material of C. jejuni biofilms and to be closely associated with bacterial lysis. Deletion mutation of the stress response genes spoT and recA enhanced the aerobic influence by stimulating lysis and increasing eDNA release. Flagella were also involved in biofilm formation but mainly contributed to attachment rather than induction of lysis. The addition of genomic DNA from either Campylobacter or Salmonella resulted in a concentration-dependent stimulation effect on biofilm formation, but the effect was not due to forming a precoating DNA layer. Enzymatic degradation of DNA by DNase I disrupted C. jejuni biofilm. In a dual-species biofilm, eDNA allocated Campylobacter and Salmonella at distinct spatial locations that protect Campylobacter from oxygen stress. Our findings demonstrated an essential role and multiple functions of eDNA in biofilm formation of C. jejuni, including facilitating initial attachment, establishing and maintaining biofilm, and allocating bacterial cells. IMPORTANCE Campylobacter jejuni is a major cause of foodborne illness worldwide. In the natural environment, the growth of C. jejuni is greatly inhibited by various forms of environmental stress, such as aerobic stress and starvation stress. Biofilm formation can facilitate the distribution of C. jejuni by enabling the survival of this fragile microorganism under unfavorable conditions. However, the mechanism of C. jejuni biofilm formation in response to environmental stress has been investigated only partially. The significance of our research is in identifying extracellular DNA released by bacterial lysis as a major form of constitution material that mediates the formation of C. jejuni biofilm in response to environmental stress, which enhances our understanding of the formation mechanism of C. jejuni biofilm. This knowledge can aid the development of intervention strategies to limit the distribution of C. jejuni.